2022
DOI: 10.1186/s12905-022-02043-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to uptake of cervical cancer screening services in low-and-middle-income countries: a systematic review

Abstract: Objectives Low-and-middle-income countries (LMICs) bear a disproportionate burden of cervical cancer mortality. We aimed to identify what is currently known about barriers to cervical cancer screening among women in LMICs and propose remedial actions. Design This was a systematic review using Medical Subject Headings (MeSH) terms in Google Scholar, PubMed, Scopus, and Web of Science databases. We also contacted medical associations and universities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 86 publications
2
53
0
Order By: Relevance
“…This inadequate male involvement is manifest in the poor female cancer screening practices of the women in LMICs [ 12 ]. Underutilization of cervical cancer screening services contributes to late diagnosis and treatment with consequent increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inadequate male involvement is manifest in the poor female cancer screening practices of the women in LMICs [ 12 ]. Underutilization of cervical cancer screening services contributes to late diagnosis and treatment with consequent increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Men’s roles in their partners’ RH experiences range from joint decision-making or granting permission to the provision of financial support and transportation [ 11 ]. Recent reviews show that lack of knowledge about female cancers and the role of screening, unsupportive partners and families, cost and fear are major barriers to screening for breast and cervical cancers among women in LMICs [ 12 , 13 ]. The need for spousal approval is also a barrier to cervical cancer screening among Nigerian women [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent systematic review on cervical cancer screening in low- and middle-income countries identified several barriers, including cultural or traditional and religious, societal, and health system or structure barriers, as well as lack of knowledge and awareness of cervical cancer in general. 14…”
Section: Screening Prevention and Diagnosismentioning
confidence: 99%
“…13 A recent systematic review on cervical cancer screening in low-and middle-income countries identified several barriers, including cultural or traditional and religious, societal, and health system or structure barriers, as well as lack of knowledge and awareness of cervical cancer in general. 14 The HPV vaccine has been shown to be effective against anogenital warts and high-grade cervical lesions. A study published in 2020 that included more than 1 million women in Sweden found that the quadrivalent HPV vaccine demonstrated a substantially reduced risk of invasive cervical cancer.…”
Section: Screening Prevention and Diagnosismentioning
confidence: 99%
“…Cervical cancer is the most common type of gynecologic cancer ( IARC, 2022 ), ranking second in cancer incidence in developing countries ( Motoki et al, 2015 ). Cervical cancer is less prevalent in high-income countries because cervical cancer screening is widely available and effective, and the human papillomavirus (HPV) vaccine is also widely available ( Petersen et al, 2022 ). Jiang et al suggested that Resveratrol may potentiate the effect of cisplatin cis-DDP (cis-dichlorodiamine-platinum (II) in the treatment of cervical cancer.…”
Section: In This Section We Briefly Introduce Each Papermentioning
confidence: 99%